Deciphering Neurodegenerative Diseases Using Long-Read Sequencing. (31st August 2021) - Su, Yun; Fan, Liyuan; Shi, Changhe; Wang, Tai; Zheng, Huimin; Luo, Haiyang; Zhang, Shuo; Hu, Zhengwei; Fan, Yu; Dong, Yali; Yang, Jing; Mao, Chengyuan; et al.
Abstract : Neurodegenerative diseases exhibit chronic progressive lesions in the central and peripheral nervous systems with unclear causes. The search for pathogenic mutations in human neurodegenerative diseases has benefited from massively parallel short-read sequencers. However, genomic regions, including repetitive elements, especially with high/low GC content, are far beyond the capability of conventional approaches. Recently, long-read single-molecule DNA sequencing technologies have emerged and enabled researchers to study genomes, transcriptomes, and metagenomes at unprecedented resolutions. The identification of novel mutations in unresolved neurodegenerative disorders, the characterization of causative repeat expansions, and the direct detection of epigenetic modifications on naive DNA by virtue of long-read sequencers will further expand our understanding of neurodegenerative diseases. In this article, we review and compare 2 prevailing long-read sequencing technologies, Pacific Biosciences and Oxford Nanopore Technologies, and discuss their applications in neurodegenerative diseases.